Training the Fetal Immune System Through Maternal Inflammation—A Layered Hygiene Hypothesis - Apostol, April C.; Jensen, Kirk D. C.; Beaudin, Anna E. (Frontiers in Immunology, 2020)
Over the last century, the alarming surge in allergy and autoimmune disease has led to the hypothesis that decreasing exposure to microbes, which has accompanied industrialization and modern life in the Western world, has fundamentally altered the immune response. In its current iteration, the 'hygiene hypothesis' suggests that reduced microbial exposures during early life restricts the production and differentiation of immune cells suited for immune regulation. Although it is now well appreciated that the increase in hypersensitivity disorders represents a ‘perfect storm’ of many contributing factors, we argue here that three important considerations have rarely been explored. First, the window of microbial exposure that impacts immune development is not limited to early childhood, but likely extends into the womb. Second, restricted microbial interactions by an expectant mother will bias the fetal immune system towards hypersensitivity. Here, we extend this discussion to hypothesize that the cell types sensing microbial exposures include fetal hematopoietic stem cells, which drive long-lasting changes to immunity.